Monopoly power upon the world of work: A workplace analysis in the logistic segment under automation - Valeria Cirillo; Francesco Massimo; Matteo Rinaldini; Jacopo Staccioli; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
This paper aims to investigate the impact of monopoly power on the world of work within the logistics sector, particularly in the context of automation processes. We conduct a fieldwork analysis of three workplaces situated in Italy, each owned by distinct types of monopolies: a conventional monopoly, Phillip Morris, the global leader in tobacco and cigarette production; a state-owned monopoly, Poste Italiane, the exclusive public provider of mail services within the national borders; and a novel form of digital monopoly that holds control over intangibles and exhibits monopsonistic control over labour - Amazon. Through a comparative examination of these three diverse forms of monopolies, utilising corporate-level metrics and patent data, we scrutinise the impact on the labour process of individuals employed in the logistics sector and affected by the implementation of automation technology, such as Automated Guided Vehicles. Employing a qualitative analysis that includes semi-structured interviews with HR professionals, IT specialists, and workers, we underscore that powerful monopolies play a crucial role in shaping the trajectory of technological development, adoption, and utilisation. Despite notable distinctions observed among the three cases, we underscore a common trend of standardisation and codification of human activities when interfacing with automated machines.
Keywords: O33; L12; J81; 330; Automation; Intangibles; Monopoly Power; Labour process; Case studies; Tasks; Organization of Work